Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1073/pnas.92.16.7352
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A biosynthesis in Rhizobium leguminosarum: role of a 2-keto-3-deoxyoctulosonate-activated 4' phosphatase.

Abstract: Lipid A from several strains of the N2-fixing bacterium Rhizobium leguminosarum displays significant structural differences from Escheriehia coli lipid A, one of which is the complete absence of phosphate groups. However, the first seven enzymes of E. coli lipid A biosynthesis, leading from UDP-GlcNAc to the phosphorylated intermediate, 2-keto-3-deoxyoctulosonate (Kdo2)-lipid IVA, are present in R. leguminosarum. We now describe a membrane-bound phosphatase in R leguminosarum extracts that removes the 4' phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 37 publications
3
59
0
Order By: Relevance
“…The R. leguminosarum lpxE structural gene encoding the 1-phosphatase has recently 2 M. Karbarz and C. R. H. Raetz, manuscript in preparation. (43,44,(55)(56)(57). The only exceptions are the reactions that incorporate the 4Ј-galacturonic acid and the ␤-hydroxybutyrate residues.…”
Section: Discussionmentioning
confidence: 99%
“…The R. leguminosarum lpxE structural gene encoding the 1-phosphatase has recently 2 M. Karbarz and C. R. H. Raetz, manuscript in preparation. (43,44,(55)(56)(57). The only exceptions are the reactions that incorporate the 4Ј-galacturonic acid and the ␤-hydroxybutyrate residues.…”
Section: Discussionmentioning
confidence: 99%
“…Assay Conditions-For mannosyltransferase reactions, unless indicated, the standard reaction mixtures (10 -40 l) contained 50 mM Hepes, pH 7.5, 0.1% Triton X-100, 10 M Kdo 2 -[4Ј- 32 (42,43). The mannosyltransferase, LpcC, is proposed to form the ␣,1-5 linkage between mannose and the inner Kdo.…”
Section: Methodsmentioning
confidence: 99%
“…2), are identical (42,43). In both systems, Kdo 2 -lipid IV A can be further acylated (2, 48 -50), but in R. leguminosarum, Kdo 2 -lipid IV Acan also be dephosphorylated at the 1-and 4Ј-positions to generate an unusual lipid A moiety lacking phosphate (23,43). In both systems, Kdo 2 -lipid IV A can also serve as an acceptor of several distinct core sugars, which are transferred one at a time from sugar nucleotide donors (18,19,23,44).…”
Section: Sequential Addition Of Mannose Galactose and Kdo To The Acmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this common lipid A precursor also implied that these rhizobial cells possess unique enzyme activities, which process their Kdo 2 lipid-IVa analog into the mature rhizobial lipid A structure. Several of these enzyme activities have been reported, including a membranebound phosphatase that removes the 4Ј-phosphate from Kdo 2 lipid-IVa and requires the presence of the Kdo residues for maximum activity (21), a second phosphatase that removes the 1-phosphate (22), and a unique acyl carrier protein required for the transfer of the 27-hydroxyoctacosanoyl residue to the lipid A (23). In addition, a rhizobial-specific mannosyl transferase activity has been identified that transfers mannose from GDPMan to Kdo 2 lipid-IVa (24).…”
mentioning
confidence: 99%